Crisis memes: The importance of templatability to Internet culture and freedom of expression. Issue 2 (1st June 2013) - Rintel, Sean
Crisis memes are the ghoulish and satirical posts that spread through social media concurrently with serious journalistic reportage. They are folk productions that respond to challenging events based on thematic and structural templates of popular online image macros. This article explores how templatability is relevant to the underpinnings, development, structure and value of crisis memes. The combination of frivolity and ghoulishness that is typical of crisis memes may be criticized for not being reasoned discourse, reinforcing cultural divides and making use of copyrighted content without permission and in ways that the copyright holder may not wish. However, the value of crisis memes lies not in their content but rather their place as a public voice that sidesteps the constraints of traditional media and as an illustration of freedom of expression that may be threatened by increasingly restrictive copyright regimes.